The Relevance of Clinical Legal Education for Law School on Preparing Legal Human Resources in Indonesia - Suhadi, Suhad (The Indonesian Journal of International Clinical Legal Education, 2019)
The demand for qualified human resources in the legal field continues to increase in response to societal needs. To produce competent legal professionals, higher legal education must shift its educational orientation. It is no longer sufficient for law schools to equip students solely with technical skills for analyzing legislation; they must also provide knowledge that enables students to understand law and justice as fundamental human needs. Clinical Legal Education (CLE) serves as a learning model that fosters interactive and reflective learning, strengthens value-sensitive approaches to legal purposes, instills a commitment to public service and social justice, and establishes the foundation for responsible legal professionalism. Through CLE, students are encouraged to engage directly with the empirical dimensions of law. This approach enriches their legalistic–formalistic understanding by exposing them to social values and real-world legal issues faced by communities. In this regard, Clinical Legal Education holds significant relevance for legal education in Indonesia, as it prepares law graduates to become competent and socially responsive human resources in the legal sector.